El fenómeno carístico en Chile - Cecioni, Giovanni (Investigaciones Geográficas: Una mirada desde el sur, 1982)
Evidences of Karst phenomenon by action of corrosion in Chile, have been recognized only in the Coastal Tarapaca Cordillera, in the Upper Paleozoic limestones of the Patagonian Archipielago and in the limestone of the El Loa Formation as well as in the clay limestones member of the Cerro Toro Formation at the Ultima Esperanza Province. The observed forms are karren, a few sink-hole type dolines, wide and flat and great uvalas. It is possible that some of these latter might correspond to poljas; however, an appropriate study of this phenomenon has never been carried out. The extration of the Guarello limestones let out cavern with sink at the roof and lateral horizontal grottos at sea level. By the action of solution, in the Atacama Andes salt deposits, two embrionary and recent sink-holes have been observed. In the Uppermost Jurassic Main Gypsum, near the Maipo Gorge, there are numerous well developed dolinas, parcially covered by a salt glacier. While at the northern chilean sector the lime karst landscape is a "fossil" feature, at the south it is very active and it has developed over limestones which really are similar to the "marmo ordinario" of Carrara, of lower most quality.